Unravelling the myotonic dystrophy type 1 clinical spectrum: A systematic registry-based study with implications for disease classification - De Antonio, M.; Dogan, C.; Hamroun, D.; Mati, M.; Zerrouki, S.; Eymard, B.; Katsahian, S.; Bassez, G. (Revue neurologique, 2016)
The broad clinical spectrum of myotonic dystrophy type 1 (DM1) creates particular challenges for both medical care and design of clinical trials. Clinical onset spans a continuum from birth to late adulthood, with symptoms that are highly variable in both severity and nature of the affected organ systems. In the literature, this complex phenotype is divided into three grades (mild, classic, and severe) and four or five main clinical categories (congenital, infantile/juvenile, adult-onset and late-onset forms), according to symptom severity and age of onset, respectively. However, these classifications are still under discussion with no consensus thus far. While some specific clinical features have been primarily reported in some forms of the disease, there are no clear distinctions. As a consequence, no modifications in the management of healthcare or the design of clinical studies have been proposed based on the clinical form of DM1. The present study has used the DM-Scope registry to assess, in a large cohort of DM1 patients, the robustness of a classification divided into five clinical forms. Our main aim was to describe the disease spectrum and investigate features of each clinical form. The five subtypes were compared by distribution of CTG expansion size, and the occurrence and onset of the main symptoms of DM1. Analyses validated the relevance of a five-grade model for DM1 classification. Patients were classified as: congenital (n=93, 4.5%); infantile (n=303, 14.8%); juvenile (n=628, 30.7%); adult (n=694, 34.0%); and late-onset (n=326, 15.9%). Our data show that the assumption of a continuum from congenital to the late-onset form is valid, and also highlights disease features specific to individual clinical forms of DM1 in terms of symptom occurrence and chronology throughout the disease course. These results support the use of the five-grade model for disease classification, and the distinct clinical profiles suggest that age of onset and clinical form may be key criteria in the design of clinical trials when considering DM1 health management and research.